87Sr, 119Sn, 127I Single and {1H/19F}‐Double Resonance Solid‐State NMR Experiments: Application to Inorganic Materials and Nanobuilding Blocks. Issue 15 (20th September 2016) - Laurencin, Danielle; Ribot, François; Gervais, Christel; Wright, Adrian J.; Baker, Annabelle R.; Campayo, Lionel; Hanna, John V.; Iuga, Dinu; Smith, Mark E.; Nedelec, Jean‐Marie; Renaudin, Guillaume; Bonhomme, Christian
Abstract: 87 Sr, 127 I and 119 Sn wideline NMR spectroscopy was successfully applied to inorganic and hybrid materials: (i) Sr derivatives of medicinal interest (Sr‐malonate, Sr‐pyrophosphates, mixed Ca, Sr‐fluoroapatites); (ii) apatitic structures acting as host matrices for iodine; and (iii) Sn‐derived oxo‐clusters which can be used as inorganic nanobuilding blocks. The BRAIN (BRoadband Adiabatic INversion) CP (Cross Polarization) approach (by Schurko et al .) was applied to a non integer quadrupolar nucleus ( 87 Sr, I=9/2). The sequence was used in combination with WURST (Wideband Uniform‐Rate Smooth‐Truncation) QCPMG (Quadrupolar Carr‐Purcell Meiboom‐Gill) for optimal sensitivity. We showed that 127 I WURST QCPMG experiments were sufficiently sensitive to allow rapid characterization of the incorporation of iodide (I − ) anions in lead vanadate/phosphate apatites, and that 127 I acted as a sensitive probe for the description of local disorder. 1 H/ 19 F → 119 Sn BRAIN CP was successfully applied to the detailed characterization of tin oxo‐clusters, using 1 H and 19 F as spin baths. We demonstrated that BRAIN CP can be effectively used as a tool of spectral editing leading to the estimation of spatial proximities between 119 Sn and 1 H/ 19 F nuclei. Abstract : Full experimental details are given for the robust set up of 87 Sr, 119 Sn and 127 I VOCS WURST (Q)CPMG BRAIN CP NMR experiments and their application to the detailed study of Sr‐derived materials, nanometric tin oxo‐cores and iodoapatites. The overall objective of this article is to extend (and make more accessible to a wide range of chemical practitioners) wideline acquisition methods (including the BRAIN‐CP sequence).